A "Signal On" Photoelectrochemical Biosensor Based on Bismuth@N, O‐Codoped‐Carbon Core‐Shell Nanohybrids for Ultrasensitive Detection of Telomerase in HeLa Cells. Issue 15 (19th December 2017) - Liu, Shanshan; Zhao, Shulin; Tu, Wenwen; Wang, Xiaoying; Wang, Xiao; Bao, Jianchun; Wang, Yu; Han, Min; Dai, Zhihui
Abstract: Core‐shell nanohybrids (NHs) with good semiconducting properties are vital to promote optoelectronic, photocatalytic, biosensing and bioelectronics technologies. Although great process has been achieved, synthesis of NHs composed of semiconductor core and heteroatom‐doped nanocarbon shell remains a challenge, and their applications in photoelectronchemical (PEC) biosensors have not been explored. Herein, the synthesis and properties of a Bi nanocrystal and N, O‐codoped carbon (NOC) core–shell NHs (Bi@NOC) is described, which exhibits the typical semiconducting feature with the bandgap of 1.14 eV. Also, such NHs show good biocompatibility and their surfaces bear the carboxylic groups that facilitate further assembly of an amino‐modified primer DNA. By taking advantage of the excellent PEC activity of Bi@NOC NHs and the signal amplification effect of thioflavine‐T, a novel "signal on" PEC aptasensor for the detection of telomerase activity is constructed. The fabricated aptasensor can detect telomerase activity from 5.0×10 2 to 1.0×10 6 HeLa cells with a low detection limit of 60 cells. Also, the aptasensor shows a wide linear response ranges, high sensitivity and good reproducibility. This work not only enriches current core–shell NHs family but also offers a novel PEC biosensing platform for detecting telomerase activity that is helpful for early clinical diagnosis of cancer. Abstract : Novel Bi@N, O‐codoped carbon core–shell nanohybrids have been synthesized, and shown the typical semiconducting feature. By taking advantage of their excellent photoelectrochemical (PEC) activity and the signal amplification effect of thioflavine‐T, a signal on PEC aptasensor for detecting telomerase in HeLa cells is further fabricated, which shows low detection limits, wide linear ranges, high sensitivity and good reproducibility.